Ethics and Arms Sales: A Discourse Analysis of Canadian Foreign Policy - Graff, David (Université d'Ottawa / University of Ottawa, 2021)
Since 2015, the Canadian government has made recurrent assertions that Canada has a feminist foreign policy. A policy, according to certain critics, that is hypocritical because of the government’s continuation of arms exports to countries deemed unsavory from a human rights standpoint. This context makes for a fertile exploration of the nexus between ethical foreign policy aspirations and the realities of foreign relations policy implementation and impact. By assessing these circumstances, I attempt to understand how hypocrisy functions within Canadian foreign policy. Through a method of discourse analysis, I evaluate the official discourses from the government and responses by civil society in relation to the Liberal Government’s handling of the Canada – Saudi Light Armoured Vehicle contract. In addition, by analysing Canadian foreign policy, via departmental reports, I highlight how the government attempts to infuse Canada’s foreign policy with ethical considerations. By tracing the rise of ethical considerations in Canada’s foreign policy, I argue that hypocrisy is intertwined with ethical considerations, thus systematically embedding hypocrisy within established Canadian institutions. Moreover, I show that Canada is committed to the concept of risk transfer, the doctrine of double effect and need for ‘proof grounded in evidence’ when assessing arms exports. These concepts shift the risks associated with hypocritical action away from the government and onto the people it purports to aid.
Keywords: Ethics; Hypocrisy; Foreign Policy; Ethical Foreign Policy; Global Affairs Canada